Analiza popytu konsumenckiego - Miszczak, Witold (The analysis of consumer demand, 2006)
Theory of consumption tries to explain why consumers will divide their incomes on goods services which satisfy their needs. Satisfaction for all consumers is measured by utility function t/(q) = pTog(q-y) and y = Q’p, 90 where P, y are some parameters and q is a vector of quantities consumed. Q = (qi, ,q*)- When we observe a p vector of prices and vector of consumers income or total expenditure, we can solve demand set equations numerically with SUR and GLS methods described in [2].
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 80-90